Hubungan Intensitas Nyeri Pada Pasien Low Back Pain dengan Kualitas Tidur di RSUD Dr. Moewardi - Sari, Nourma Yustia; , dr. Flora Ramona S.P, M.Kes.,Sp.KK; , dr. Budi Hernawan (2015)
Background: Low Back Pain is one of the most common musculoskeletal disorders that occur in everyday practice. Low Back Pain is defined as pain that is felt in the lower back region, can be a local pain and radicular pain is usually accompanied by reduced mobility due to pain caused. Low Back Pain is a major problem in the world, millions of money spent each year to deal with LBP, often have limited success due to the high intensity of the pain inflicted. Low Back Pain is the second highest after visiting cephalgia Neurology Clinic in Indonesia.. Purpose: Explain the relationship LBP pain intensity in the patient with sleep quality in hospitals Dr. Moewardi. Method: Observational study of cross sectional analytic approach to obtain 64 patients, consisted of 32 patients diagnosed with LBP pain score 0-5 and 32 patients diagnosed with LBP pain score 6-10. Sampling by using random sampling. Result: Data were analyzed using Chi square test p value = 0.048 (p <0.05) for LBP. Conclusion: Based on the research that has been done p value = 0.048 (p <0.05) for LBP can be concluded that there is a significant relationship between pain intensity in patients with LBP with sleep quality in hospitals Dr. Moewardi. Low Back Pain pain score 6-10 more at risk of sleep disturbance 3 times greater than the LBP pain score 0-5.